(untitled) - Pontier, Jannet Adriana (The Hague, 2004)
The European rules on jurisdiction and recognition and enforcement of judgments in civil and commercial matters, laid down in EU Regulation (44/2001), are of great practical importance. Preliminary considerations to the Regulation imply that decisions in which the ECJ has interpreted the Brussels Convention remain relevant for the interpretation of the Regulation. Therefore, to have a thorough understanding of the Regulation, an in-depth knowledge of the EC Court's case law regarding the Brussels Convention is imperative. It appears that the significance of the Court's case law lies in both the final outcome of its decisions, and in the principles that it consistently refers to in arriving at these decisions. The authors piece together the system of principles that has become apparent in the Court's reasoning. An understanding of this system enables lawyers to understand the confines within which the Court's argumentation is likely to take place in future cases.
Keywords: Court of Justice of the European Communities,Judicial assistance,Judgments, foreign,Jurisdiction; European union countries,European union countries,European union countries